2021
DOI: 10.21053/ceo.2019.01382
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Related to Cognitive Impairment After Hearing Loss

Abstract: Objectives. Our research group has previously demonstrated that hearing loss might be a risk factor for synaptic loss within the hippocampus and impairment of cognition using an animal model of Alzheimer disease. In this study, after inducing hearing loss in a rat model of Alzheimer disease, the associations of various microRNAs (miRNAs) with cognitive impairment were investigated. Methods. Rats were divided randomly into two experimental groups: the control group, which underwent sham surgery and subthreshold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…In the analysis of GSE45026, we only selected C57 mice for analysis, because C57 mice have a clear phenomenon of senile hearing loss. In previous studies, Mun found that the expression of miR-29b-3p was elevated in the cochlea of aged C57BL/6 mice [28], which was consistent with our analysis. For others, miR-29a-3p, miR-29c-3p and miR-124-3p were mainly related to cancer [29][30][31][32][33][34], AD [35,36], and miR-124-3p also related to neurogenesis [37,38] and depression [39], with no research related to hearing loss.…”
Section: Discusssupporting
confidence: 93%
“…In the analysis of GSE45026, we only selected C57 mice for analysis, because C57 mice have a clear phenomenon of senile hearing loss. In previous studies, Mun found that the expression of miR-29b-3p was elevated in the cochlea of aged C57BL/6 mice [28], which was consistent with our analysis. For others, miR-29a-3p, miR-29c-3p and miR-124-3p were mainly related to cancer [29][30][31][32][33][34], AD [35,36], and miR-124-3p also related to neurogenesis [37,38] and depression [39], with no research related to hearing loss.…”
Section: Discusssupporting
confidence: 93%
“…We postulated that previous statin use may have a protective effect against hearing impairment. Hearing impairment in the adult population could have multiple etiologies, such as age-related degenerative processes, noise exposure, ototoxic drug exposure, smoking, adiposity, and chronic diseases 13 15 . To encompass all these types of hearing impairment, this study collected data from a nationally registered hearing-impaired population and compared the previous statin use in this population to that in the control population.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent studies have shown a relationship between cognitive decline and miRNAs in AD. In a rat model of AD, several miRNAs were found to be involved in cognitive deficits after hearing loss [ 10 ]. Another study using aged Tg4-42 mice, a sporadic AD model revealed alterations in hippocampal miRNAs after memory decline [ 11 ].…”
Section: Introductionmentioning
confidence: 99%